CASES OF VIOLENCE AGAINST WOMEN HANDLED BY SENTRA PARAMITA MATARAM - Lalu Wahyu Harits Aswili; Elly Malihah; Siti Nurbayani (Universitas Negeri Medan, 2023)
Various forms of societal violence often target women, causing significant impacts on well-being and requiring substantial recovery efforts. This research aims to comprehensively explain the different forms of violence against women in Sentra Paramita Mataram. The study employs a descriptive method with a qualitative approach, enabling an in-depth exploration of experiences and perceptions of victims and a better understanding of the context of the violence. Primary subjects are women who have been victims of violence in Sentra Paramita Mataram, with social workers, psychologists, and nurses as informants. This approach allows for a thorough examination of the experiences and perceptions of victims, providing a nuanced understanding of the dynamics of violence against women in this specific setting. Data collection methods include in-depth interviews, observations, and documentation. The data analysis process involves presenting data, reducing data, verifying information, and drawing conclusions. Study findings reveal that the most prevalent form of violence against women in Sentra Paramita Mataram is physical violence, including actions such as causing injuries, physical assaults, torture, and rape. Non-physical incidents of violence against women, such as verbal abuse, harassment, involvement in commercial sex work, and neglect, also receive attention. Both physically and non-physically experienced violence compels victims to seek immediate assistance at Sentra Paramita Mataram, underscoring the urgent role of the center as a support and protection hub for victims. This research contributes to a profound understanding of the dynamics of violence against women in this environment and lays the groundwork for more effective intervention and prevention measures.